Occurrence, biology, damage potential and management of Heterodera Schachtii (Nematoda: Heteroderidae) in small-scale farming in the Western Cape Province, South Africa - Van Zyl, J. (Jacques) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD (Agric))--University of Stellenbosch, 2003.